Quick flicks: association of paroxysmal kinesigenic dyskinesia and tics - Balint, Bettina (Movement disorders clinical practice, 2018)
Background: Paroxysmal kinesigenic dyskinesia (PKD) is a rare disorder characterised by brief attacks of chorea, dystonia, or mixed forms precipitated by sudden movement. Methods: Observational study with a cohort of 14 PKD patients and genetic testing for PRRT2 mutations. Results: In a series of 14 PKD patients seen in our clinic at the National Hospital of Neurology, Queen Square, from 2012-2017, we noted tics in 11 patients (79%), which stand in stark contrast to the estimated lifetime prevalence of tics estimated to reach 1%. Conclusions: The two reasons to point out this possible association are the clinical implications and the potential opportunity of a better understanding of shared pathophysiological mechanisms of neuronal hyperexcitability.
Gesehen am 03.04.2020